Arabidopsis apoplast TET8 positively correlates to leaf senescence, and tet3tet8 double mutants are delayed in leaf senescence - Jayde A. Zimmerman; Benjamin Verboonen; Andrew P. Harrison Hanson; Luis R. Arballo; Judy A. Brusslan (Plant Direct)
Abstract Extracellular vesicles (EVs) are membrane‐bound exosomes secreted into the apoplast. Two distinct populations of EVs have been described in Arabidopsis: PEN1‐associated and TET8‐associated. We previously noted early leaf senescence in the pen1 single and pen1pen3 double mutant. Both PEN1 and PEN3 are abundant in EV proteomes suggesting that EVs might regulate leaf senescence in soil‐grown plants. We observed that TET8 is more abundant in the apoplast of early senescing pen1 and pen1pen3 mutant rosettes and in older wild‐type (WT) rosettes. The increase in apoplast TET8 in the pen1 mutant did not correspond to increased TET8 mRNA levels. In addition, apoplast TET8 was more abundant in the early leaf senescence myb59 mutant, meaning the increase in apoplast TET8 protein during leaf senescence is not dependent on pen1 or pen3. Genetic analysis showed a significant delay in leaf senescence in tet3tet8 double mutants after 6 weeks of growth suggesting that these two tetraspanin paralogs operate additively and are positive regulators of leaf senescence. This is opposite of the effect of pen1 and pen1pen3 mutants that show early senescence and suggest PEN1 to be a negative regulator of leaf senescence. Our work provides initial support that apoplast‐localized TET8 in combination with TET3 positively regulates age‐related leaf senescence in soil‐grown Arabidopsis plants.